Analysis of aging factor effect from BLEVE fireball impact at dynamic parameter condition / Abang Amrun Abang Bussri - Abang Bussri, Abang Amrun (2019)
The probability of burn victim survival from BLEVE fireball impacts during the transportation of LPG can be estimated by understanding the thermal radiation model and the consequences of BLEVE towards human. The sequence of a BLEVE fireball event is been analysed in collecting the factors that effecting the severity of victims during the occurrences of BLEVE. Solid flame model has been used in this simulation to obtain all the characteristics of the fireballs. All the models related has been distinguished to fiend which one is more appropriate and contains more information related to the studies. Lynchburg, Virginia has been chosen as the location of the study. Thermal radiation by solid flame model is taken as the main parameter to be compared with tables and figures in determining the consequences of a BLEVE event. Different chances of survival probability are discussed based on a few elements such as distance, time, age and total burn body surface area.